Genetic diversity of Pseudo-nitzschia brasiliana (Bacillariophyceae) from Malaysia - Hong, C.L; Po, T.L; Su, S.N.P; Sing, T.T; Chui, P.L (Springer Netherlands, 2012)
To clarify the genetic diversity of a potentially toxic pennate diatom, Pseudo-nitzschia brasiliana found in Malaysian waters, 30 strains of P. brasiliana were established into clonal culture since May 2008. The ultrastructure of these strains was examined for confirmation of species identification. The genetic marker, internal transcribed spacer (ITS) of nuclear-encoded ribosomal DNA was used to examine the genetic diversity of P. brasiliana isolated from different geographical localities. The ITS sequences of P. brasiliana were highly conserved in their secondary structures, with five helices in the first internal transcribe spacer (ITS1) and four universal helices in the second internal transcribe spacer (ITS2) with a pseudo-helix. No compensatory base change was observed among the strains examined. Genetic divergences among the Malaysian strains ranged from 0.07% to 0.54%. The present study revealed a high genetic homogeneity of Malaysian P. brasiliana strains.